M2a macrophage can rescue proliferation and gene expression of benign prostate hyperplasia epithelial and stroma cells from insulin‐like growth factor 1 knockdown. Issue 9 (16th April 2021) - Qian, Qiaofeng; He, Weixiang; Liu, Daoquan; Yin, Jing; Ye, Linpeng; Chen, Ping; Xu, Deqiang; Liu, Jianmin; Li, Yan; Zeng, Guang; Li, Mingzhou; Wu, Zhonghua; et al.
Abstract: Background: Benign prostatic hyperplasia (BPH) is a common disease in elderly men and is often accompanied by chronic inflammation. Macrophages (several subtypes) are the main inflammatory cells that infiltrate the hyperplastic prostate and are found to secrete cytokines and growth factors. The current study aims to explore the effect of M2a macrophages on the development of BPH via insulin‐like growth factor 1 (IGF‐1). Methods: Human prostate tissues, prostate, and monocyte cell lines (WPMY‐1, BPH‐1, and THP‐1) were used. THP‐1 was polarized into several subtypes with cytokines. The expression and localization of IGF‐1 and M2 macrophages were determined via immunofluorescent staining, quantitative real‐time polymerase chain reaction, and Western blot analysis. Flow cytometry and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) assays were used to investigate the effects of different subtypes of macrophages on prostate cells. IGF‐1 in WPMY‐1 and BPH‐1 cells was silenced and cocultured with or without M2a macrophages. Cell proliferation, apoptosis, cell cycle, epithelial–mesenchymal transition (EMT), and fibrosis processes were examined. Results: The polarized subtypes of macrophages were verified by amplifying their specific markers. M2a macrophages enhanced prostate cell proliferation more significantly and CD206 was more expressed in hyperplastic prostate. IGF‐1 was localized in both epithelial and stromal components of prostate and upregulated in BPH tissues. M2a macrophages expressed more IGF‐1 than other subtypes. Knockdown of IGF‐1 in WPMY‐1 and BPH‐1 cells attenuated cell proliferation, promoted cell apoptosis, retarded cell cycle at the G0/G1 phase, and suppressed the EMT process in BPH‐1 cells as well as the fibrotic process in WPMY‐1 cells, which was reversible when cocultured with M2a macrophages. Conclusion: These data demonstrated that knockdown of IGF‐1 expression in cultured BPH epithelial and stromal cells reduces proliferation and increases apoptosis. These effects are reversed by coculture with M2a macrophages.